Kearifan Lokal Seni Benjang Sebagai Sumber Belajar Pada Mata Pelajaran Sosiologi - Aulia, Vina; Wildan, Dadan; Komariah, Siti (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2024)
Benjang art as the local wisdom of the Ujung Berung community began to experience strong competition with shows or entertainment that came from abroad. This condition threatens the existence of Benjang art in the current generation so that there needs to be a cultural transfer process so that the existence of Benjang art is maintained. This study aims to further analyze how local wisdom based on Benjang art can be integrated in sociology learning in order to maintain cultural existence and carry out the process of cultural transfer between generations. The method used is a literature study by referring to several journal articles and proceedings that are relevant to the theme of the study. The research shows that there is good potential for the Benjang Art in maintaining its existence through sociology learning which can be utilized as a learning resource, especially in the material of local wisdom and community empowerment. With an ethnopedagogy-based strategy, it can be a process of transferring culture between generations, one of which is in order to maintain the existence of Benjang art as local wisdom.